Advances in cold-adapted enzymes derived from microorganisms - Liu, Yehui; Zhang, Na; Ma, Jie; Zhou, Yuqi; Wei, Qiang; Tian, Chunjie; Fang, Yi; Zhong, Rongzhen; Chen, Guang; Zhang, Sitong (Frontiers in Microbiology, 2023)
Cold-adapted enzymes, produced in cold-adapted organisms, are a class of enzyme with catalytic activity at low temperatures, high temperature sensitivity, and the ability to adapt to cold stimulation. These enzymes are largely derived from animals, plants, and microorganisms in polar areas, mountains, and the deep sea. With the rapid development of modern biotechnology, cold-adapted enzymes have been implemented in human and other animal food production, the protection and restoration of environm ents, and fundamental biological research, among other areas. Cold-adapted enzymes derived from microorganisms have attracted much attention because of their short production cycles, high yield, and simple separation and purification, compared with cold-adapted enzymes derived from plants and animals. In this review we discuss various types of cold-adapted enzyme from cold-adapted microorganisms, along with associated applications, catalytic mechanisms, and molecular modification methods, to establish foundation for the theoretical research and application of cold-adapted enzymes.